Determinants of acquired activated protein C resistance and D-dimer in breast cancer. Issue 145 (September 2016) - Tinholt, Mari; Sandset, Per Morten; Mowinckel, Marie-Christine; Garred, Øystein; Sahlberg, Kristine Kleivi; Kristensen, Vessela N.; Børresen-Dale, Anne-Lise; Jacobsen, Anne Flem; Skretting, Grethe; Iversen, Nina
Abstract: Background: We have previously reported acquired activated protein C (APC) resistance and elevated plasma D-dimer levels in breast cancer patients. Here, we aimed to identify phenotypic and genetic determinants that contribute to the acquired APC resistance and increased D-dimer levels in breast cancer. Healthy controls served as reference. We also addressed whether higher APC resistance or D-dimer levels could be potential markers of clinicopathological breast cancer characteristics. Materials and methods: 358 breast cancer patients and 273 healthy controls were enrolled and hemostatic plasma parameters were determined; factor (F) V, FVIII, FIX, FX, fibrinogen, von Willebrand factor (VWF), normalized APC sensitivity ratio (n-APC-sr), protein C, protein S, antithrombin, tissue factor pathway inhibitor (TFPI), and D-dimer. Common single nucleotide polymorphisms were genotyped in coagulation-related genes in the breast cancer patients. Results: The phenotypic hemostatic factors explained 25% and 31% of the variability in acquired APC resistance and D-dimer levels, respectively, in the breast cancer patients. Fibrinogen (β = − 0.35, P  < 0.001), protein C (β = 0.28, P  < 0.001), and FIX (β = 0.22, P  = 0.026) were identified as determinants of n-APC-sr (in FV Leiden non-carriers), whereas TFPI (β = 0.28, P  < 0.001), antithrombin (β = − 0.25, P  < 0.001), and FX (β = 0.15, P  = 0.040) were the major determinants of D-dimer. Moreover, borderline higher APC resistance (> 75th percentile) was found in patients with triple negative tumors (odds ratio (OR) 1.97, 95% CI 0.99–3.90). Conclusions: This study reports phenotypic hemostatic parameters that determine acquired APC resistance and D-dimer levels in breast cancer patients. The explanatory power was modest, however, our findings are hypothesis generating and may contribute to further understand the background for cancer associated-coagulopathy and thrombosis. Highlights: Fibrinogen, protein C, and FIX were identified as determinants of acquired APC resistance in breast cancer patients. TFPI, antithrombin, and FX were identified as determinants of D-dimer in breast cancer patients. A tendency towards higher APC resistance was found in breast cancer patients with triple negative tumors.